Global, regional, and national time trends in mortality for congenital heart disease, 1990–2019: An age-period-cohort analysis for the Global Burden of Disease 2019 study. (January 2022) - Su, Zhanhao; Zou, Zhiyong; Hay, Simon I.; Liu, Yiwei; Li, Shoujun; Chen, Huiwen; Naghavi, Mohsen; Zimmerman, Meghan S.; Martin, Gerard R.; Wilner, Lauren B.; Sable, Craig A.; Murray, Christopher J L; et al.
Summary: Background: Congenital heart disease (CHD) is the leading cause of morbidity and mortality from birth defects worldwide. We report an overview of trends in CHD mortality in 204 countries and territories over the past 30 years and associations with age, period, and birth cohort. Methods: Cause-specific CHD mortality estimates were derived from the Global Burden of Disease 2019 study. We utilised an age-period-cohort model to estimate overall annual percentage changes in mortality (net drifts), annual percentage changes from 0 to 4 to 65–69 years (local drifts), period and cohort relative risks (period/cohort effects) between 1990 and 2019. This approach allows for the examination and differentiation of age, period, and cohort effects in the mortality trends, with the potential to identify disparities and treatment gaps in cardiac care. Findings: CHD is the leading cause of deaths from non-communicable diseases (NCDs) in those under 20 years. Global CHD deaths in 2019 were 217, 000 (95% uncertainty interval 177, 000–262, 000). There were 129 countries with at least 50 deaths. India, China, Pakistan, and Nigeria had the highest mortality, accounting for 39.7% of deaths globally. Between 1990 and 2019, the net drift of CHD mortality ranged from –2.41% per year (95% confidence interval [CI] –2.55, –2.67) in high Socio-demographic Index (SDI) countries to –0.62% per year (95% CI: –0.82, –0.42) in low-SDI countries. Globally, there was an emerging transition in the age distribution of deaths from paediatric to adult populations, except for an increasing trend of mortality in those aged 10–34 years in Mexico and Pakistan. During the past 30 years, favourable mortality reductions were generally found in most high-SDI countries like South Korea (net drift = –4.0% [95% CI –4.8 to –3.1] per year) and the United States (–2.3% [–2.5 to –2.0]), and also in many middle-SDI countries like Brazil (–2.7% [–3.1 to 2.4]) and South Africa (–2.5% [–3.2 to –1.8]). However, 52 of 129 countries had either increasing trends (net drifts ≥0.0%) or stagnated reductions (≥–0.5%) in mortality. The relative risk of mortality generally showed improving trends over time and in successively younger birth cohorts amongst high- and high-middle-SDI countries, with the exceptions of Saudi Arabia and Kazakhstan. 14 middle-SDI countries such as Ecuador and Mexico, and 16 low-middle-SDI countries including India and 20 low-SDI countries including Pakistan, had unfavourable or worsening risks for recent periods and birth cohorts. Interpretation: CHD mortality is a useful and accessible indicator of trends in the provision of congenital cardiac care both in early childhood and across later life. Improvements in the treatment of CHD should reduce the risk for successively younger cohorts and shift the risk for all age groups over time. Although there were gains in CHD mortality globally over the past three decades, unfavourable period and cohort effects were found in many countries, raising questions about adequacy of their health care for CHD patients across all age groups. These failings carry significant implications for the likelihood of achieving the Sustainable Development Goal targets for under-5 years and NCD mortality. Funding: Supported by the National Natural Science Foundation of China (81525002, 31971048, 82073573 to ZZ and HZ), Shanghai Outstanding Medical Academic Leader program (2019LJ22 to HZ), and Collaborative Innovation Program of Shanghai Municipal Health Commission (2020CXJQ01 to HZ), the Bill & Melinda Gates Foundation for the Global Burden of Disease Project (to NJK) and NHMRC fellowship administered through the University of Melbourne (to GCP).